Design of a secure system of smart objects for the journey and wait of buses in Costa Rica - De-Vries-Gamboa, Nicole (2021)
According to the research carried out, it was proved the existence of many deficiencies in the public transport service in Costa Rica, such as the perception of insecurity, which left a great possibility to design smart objects that help solving this problem. After carrying out tests to determine the most relevant needs and requirements, the creation of OS bus stop and OS bus sign was proposed. Both objects provide security by having lighting and a camera. The bus stop allows access to information concerning the service and has an emergency button. While the bus sign (located on the route) shows the direction in which the different OS bus stops are located. Also, a GPS was added to the buses, so their location, and waiting time can be accessed from the bus stops. The OS bus stop has an intelligent assistant on the screen to provide a guide for those who don’t know how to use the system, allowing the users to learn the use of the interface faster, and in case of any doubt they can get answers during the process. For this project, six stages were completed, corresponding to the fundamental phases of the project process. Once the concept, the design and the process to solve its development as a product had been raised, a virtual validation of the product was carried out, through the design simulation presented in a video. This, in order to verify the aspects of the stages worked and get a synthesis of the system.